Highly Sensitive Electrochemical Determination of Norepinephrine Using Poly Acrylic Acid‐Coated Nanoceria. Issue 17 (10th September 2019) - Son, Seong Eun; Ko, Euna; Tran, Van‐Khue; Hur, Won; Choi, Hyun; Lee, Han Been; Park, Yosep; Seong, Gi Hun
Abstract: We synthesized a poly acrylic acid‐coated nanoceria (PNC) and developed colorimetric and electrochemical methods for determining norepinephrine (NE) using 3, 3′‐5, 5′‐tetramethylbenzidine (TMB) as a redox marker. The PNC was the nanozyme, an oxidase mimic with effective catalytic activity. During the reaction, PNC oxidized the TMB (TMBox ) in the absence of hydrogen peroxide. The product not only showed visible color change from transparent to blue, but also generated an electrochemical current. NE reduced the TMBox, and the color changed from blue back to colorless. As a result, we were able to determine the NE concentration using both colorimetric and electrochemical methods. The colorimetric determination showed a linearity from 0.2 to 19 μM, with an estimated detection limit of 126 nM. For point‐of‐care applications, NE concentration was also detected on paper‐based devices. NE was detected from 1.0 to 25 μM with the detection limit of 863 nM. For electrochemical detection, gold nanoparticles were deposited on indium tin oxide glass as the working electrode. NE ranged from 0.1 to 300 μM, with an estimated detection limit of 66 nM, which was lower than for the colorimetric methods. Spike recovery values for NE in human plasma samples ranged from 93.4 to 108 %. These results demonstrate that using PNC nanozymes for electrochemical detection is a promising assay to determine NE. Abstract : Nanozyme: Poly acrylic acid‐coated nanoceria (PNC) with an oxidase‐like activity is synthesized and used for highly sensitive determination of norepinephrine by colorimetric and electrochemical methods.